A global barley panel revealing genomic signatures of breeding in modern Australian cultivars. - Hill, Camilla Beate; Angessa, Tefera Tolera; Zhang, Xiao-Qi; Chen, Kefei; Zhou, Gaofeng; Tan, Cong; Wang, Penghao; Westcott, Sharon; Li, Chengdao (2021)
The future of plant cultivar improvement lies in the evaluation of genetic resources from currently available germplasm. Today's gene pool of crop genetic diversity has been shaped during domestication and more recently by breeding. Recent efforts in plant breeding have been aimed at developing new and improved varieties from poorly adapted crops to suit local environments. However, the impact of these breeding efforts is poorly understood. Here, we assess the contributions of both historical and recent breeding efforts to local adaptation and crop improvement in a global barley panel by analysing the distribution of genetic variants with respect to geographic region or historical breeding category. By tracing the impact breeding had on the genetic diversity of barley released in Australia, where the history of barley production is relatively young, we identify 69 candidate regions within 922 genes that were under selection pressure. We also show that modern Australian barley varieties exhibit 12% higher genetic diversity than historical cultivars. Finally, field-trialling and phenotyping for agriculturally relevant traits across a diverse range of Australian environments suggests that genomic regions under strong breeding selection and their candidate genes are closely associated with key agronomic traits. In conclusion, our combined dataset and germplasm collection provide a rich source of genetic diversity that can be applied to understanding and improving environmental adaptation and enhanced yields.